2009
DOI: 10.1002/ajpa.21039
|View full text |Cite
|
Sign up to set email alerts
|

Not so fast: Speed effects on forelimb kinematics in cercopithecine monkeys and implications for digitigrade postures in primates

Abstract: Terrestrial mammals are characterized by their digitigrade limb postures, which are proposed to increase effective limb length (ELL) to achieve preferred or higher locomotor speeds more efficiently. Accordingly, digitigrade postures are associated with cursorial locomotion. Unlike most medium- to large-sized terrestrial mammals, terrestrial cercopithecine monkeys lack most cursorial adaptations, but still adopt digitigrade hand postures. This study investigates when and why terrestrial cercopithecine monkeys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 110 publications
(145 reference statements)
4
77
1
Order By: Relevance
“…Specifically, faster trials were those with stance durations of <20 video fields, whereas slower trials had stance phases lasting >30 video fields (video recorded at 60Hz; see below). As seen in prior studies (Patel, 2009;Patel, 2010a), this dichotomy in speed selection corresponded well with the hand posture used by both animals: digitigrade postures were used when moving slowly and palmigrade-like postures were used when moving more quickly. One important point that must be noted is that the behavioral preferences of the subjects coupled with variable success in EMG recording resulted in unequal samples of step cycles analyzed for each muscle and for each behavior (Table1).…”
Section: Methodssupporting
confidence: 72%
See 3 more Smart Citations
“…Specifically, faster trials were those with stance durations of <20 video fields, whereas slower trials had stance phases lasting >30 video fields (video recorded at 60Hz; see below). As seen in prior studies (Patel, 2009;Patel, 2010a), this dichotomy in speed selection corresponded well with the hand posture used by both animals: digitigrade postures were used when moving slowly and palmigrade-like postures were used when moving more quickly. One important point that must be noted is that the behavioral preferences of the subjects coupled with variable success in EMG recording resulted in unequal samples of step cycles analyzed for each muscle and for each behavior (Table1).…”
Section: Methodssupporting
confidence: 72%
“…baboons) adopt digitigrade hand postures only during slow walking, and use less digitigrade or more 'palmigrade'-like hand postures (i.e. the forepaw equivalent to plantigrade hindfoot postures) when running and using asymmetrical gaits (Patel, 2009;Patel, 2010a;Patel and Polk, 2010;Patel and Wunderlich, 2010). These primates transition to palmigrady at faster speeds because of the inability of their mobile distal forelimb joints to passively resist extension moments at the wrist joint while experiencing higher GRFs -effectively forced palmigrady (Patel, 2009;Patel, 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose five locomotor categories to examine, including palmigrade/digitigrade quadrupedalism (QUAD), knuckle-walking (KW), brachiation (BRAC), vertical climbing (VC), and overall substrate usage (SUB), and assigned taxa values based on published reports of the proportion of time species spend performing different behaviors. Palmigrade and digitigrade hand postures used during quadrupedalism were grouped into the same category since recent studies have shown variation in use of these hand postures within a species, and metacarpal traits do not always clearly distinguish between ''palmigrade'' and ''digitigrade'' quadrupeds (Patel, 2009(Patel, , 2010Patel and Polk, 2010). Extant taxa were not assigned to a single locomotor category.…”
Section: Methodsmentioning
confidence: 99%